Gut and gill content analysis of the green mussel perna viridis (Linnaeus, 1758) using PCR and microscopy - Adao, Davin Edric V. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2013)
Food selectivity in bivalves may depend on many factors. Size and chemical cues (e.g.,toxicity) of food particles are probable major factors in food selection of the green mussel, perna viridis (Linnaeus 1758). Polymerase chain reaction (PCR) using genus- and species-specific primer were used together with microscopy to determine the composition of the diet of the green mussel.